Aplication of Qur’an Kemenag in Learning Islamic Religious Education in Madrasah in West Aceh - Faisal, Muhammad; Hasan, Khairuddin; Hillah, Fatta; Rahim, Reynaldi Aulia; Fadli, Nazar (AT-TURATS, 2024)
The purpose of this study is to see the benefits of the application of the Qur'an Kemenag to the learning of Islamic Religious Education in madrassas located in West Aceh Regency. As is known in today's globalization era, the world of technology and communication continues to develop. The influence of this development has an impact on all aspects of human life, including in the joints of education. The Islamic education sector is at the madrasah level in West Aceh district. The use of the Quran Kemenag aplication in the PAI learning process has a significant impact where the values of Islamic education in the Quran are easy to understand by students that using the Qur'an Application developed by the Ministry of Religious Affairs of the Republic of Indonesia in collaboration with related institutions. This application offers several features that facilitate Access to understand the verses of the Qur'an in exploring the values of Islamic education. Based on the results of research that has been conducted, this application is very useful for students in the madrasah environment of West Aceh district. Because the features offered in this application are very helpful for students to understand the educational values contained in the Qur'anic Verses.Tujuan penelitian untuk melihat manfaat penerapan Al-Qur'an Kemenag terhadap pembelajaran pendidikan agama Islam di madrasah yang terletak di Kabupaten Aceh Barat. Seperti diketahui di era globalisasi saat ini, dunia teknologi dan komunikasi terus mengalami perkembangan. Pengaruh perkembangan tersebut berdampak pada seluruh aspek kehidupan manusia, termasuk dalam sendi-sendi pendidikan. Sektor pendidikan Islam berada pada tingkat madrasah di Kabupaten Aceh Barat. Penggunaan Aplikasi Al-Qur'an Kemenag dalam proses pembelajaran PAI memberikan dampak yang signifikan, menjadikan nilai-nilai pendidikan Islam dalam Al-Quran mudah dipahami oleh siswa yang menggunakan aplikasi Al-Qur'an yang dikembangkan oleh Kementerian Agama Republik Indonesia bekerja sama dengan institusi lainnya. Aplikasi tersebut menawarkan beberapa fitur yang memudahkan akses untuk memahami ayat-ayat Al-Qur'an dalam menggali nilai-nilai pendidikan Islam. Berdasarkan hasil penelitian, aplikasi Al-Qur'an Kemenag sangat bermanfaat bagi siswa di lingkungan madrasah Kabupaten Aceh Barat. Sebab fitur-fitur yang ditawarkan pada aplikasi sangat membantu para pelajar untuk memahami nilai-nilai pendidikan yang terkandung dalam Al-Qur'an.